Pengaruh Marketing Mix Dan Perilaku Konsumen Terhadap Keputusan Pembelian Di Minimarket - Siti Nurjanah; Feti Fatimah; Akhmad Fahrur Rozi (STIE Mandala Jember, 2022)
This study aims to determine and analyze the influence of marketing mix and consumer behavior on decisions partially. The theories used in this research are marketing management theory, marketing mix theory, and consumer behavior. This research was conducted on consumers. This type of research is quantitative using purposive sampling method using a sample of 120 respondents. This study uses non-probability sampling as a sampling technique. by using a multiple linear regression test tool, which uses the SPSS software version. Based on the results of the partial test, it can be concluded that the marketing mix variable has a significant effect on purchasing decisions at the Bin Hasyi Tegalsari Minimarket and the consumer behavior variable has a significant effect on purchasing decisions at the Bin Hasyi Tegalsari Minimarket. Keywords: Marketing Mix, Consumer Behavior, Purchase Decision